HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG KEBERSIHAN GIGI DAN MULUT DENGAN TINGKAT KEBERSIHAN GIGI DAN MULUT SISWA SD USIA 10-12 TAHUN (SD Kemala Bhayangkari Kecamatan Jaya Baru Kota Banda Aceh) - Cut Fera Novita; Poppy Andriany; Syarifah Indah Maghfirah (Journal of Syiah Kuala Dentistry Society, 2016)
Maintenance of oral hygiene is one way to improve health because it can prevent the occurence of disease in the oral cavity. The children are still very dependent on their parents in terms of dental hygiene. The parents knowledge is very important in the formation of the underlying behaviors that support children oral hygiene. This study aim is to identify the relationship between mothers knowledge and childrens oral hygiene status. The research design that using is analytic cross sectional method. The research subjects are students age 10-12 years elementary school Kemala Bhayangkari Banda Aceh. The subjects were selected using total sampling and total subjects are 60 students. Based on the result of the Spearman Correlation is significancy at 0,000, it means a relationship between mothers knowledge and childrens oral hygiene status. Correlation value of 0,638, indicating that direction of a positive correlation with the strength of a strong correlation.Keywords: Mothers Knowledge, Childrens Oral Hygiene Status, Elementary Students